Utilization of AR as Learning Media for Photosynthesis to Improve Understanding of Science Concepts - Moh Ilham Yusuf; Tabitha Sri Hartati Wulandari (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
The use of technology is currently increasingly widespread, one of which is the use of AR in creating learning media. Expanding information from printed advertising materials to promotional media in videos can be done using augmented reality (AR) technology. This study aims to determine how using augmented reality (AR) as a learning medium for photosynthesis can improve understanding of scientific ideas. This study uses a research and development (R&D) method with a qualitative and quantitative approach. The sample in this study was Class VIII F of SMP Negeri 2 Tuban. The data collection technique used pretest and posttest photosynthesis material. The data analysis technique, the average percentage value of the pretest and posttest, was then analyzed using the N-Gain test score equation. The results of using AR in science learning have a lot of influence on learning activities in the classroom. Students feel more involved and motivated, while teachers find it easier to explain science concepts. Therefore, applying augmented reality technology learning to SMP Negeri 2 Tuban students can be used as a new, fun teaching material